(untitled) (Medical Forum Monthly, 2022)
Objective: To find the incidence of dry socket among tooth extraction cases operated in Islam Dental College Sialkot. Study Design: Retrospective study Place and Duration of Study: This study was conducted at the Oral and maxillofacial surgery department of Islam Dental College Sialkot from 1st January 2020 to 31st December 2021. Materials and Methods: Patient records of extraction and follow up from last two years were assessed and incidence of dry socket was calculated. The various factors like gender, mode of extraction and post operative use of antibiotic was also assessed using statistical analysis. Results: Out of 940 patients, 52 patients were diagnosed with dry socket and managed post-operatively. Surgical extraction had higher incidence (21.7%) than simple extraction (4.2%). Conclusion: The incidence of dry socket after surgical extraction, female patients and smokers is relatively higher incidence of dry socket whereas the patients who took antibiotics post-operatively had less chances of developing this complication.